The projects for the baroque Town hall of Amsterdam before 1648 (Bulletin KNOB, 1993)
Before building on the Amsterdam Town Hall was started in 1648 in accordance with the design of Jacob van Campen, a whole range of different plans had been manufactured for at least eight years. Eight of these plans, of divergent character, are now known. In one case just a rough draft of a ground plan has come down to us, in a second case a carefully worked out facade, in a third a completely elaborated design.Some were made by Van Campen himself, others by the architect Philip Vingboons, one possibly by Cornelis Danckerts de Ry, and several of them anonymous, the author still being uncertain. The names of famous connoisseurs of classical architecture have been suggested as authors, such as Pieter Post and Constantijn Huygens. Apart from their authorship, the correct date of most of these projects was also highly problematic. Consequently, their logical sequence has been the object of scholarly debate for many decades.Nevertheless, this has not resulted in a generally accepted chronology so far, although the most recent, suggested by Koen Ottenheym in his book about Vingboons, is to be regarded as the most probable. For the best skeleton for dating the undated designs is given by the successive resolutions of the 'Vroedschap' (town council), which in the period 1639-1648 changed the measurements for the new town hall that they wanted to build several times.These measurements were published for the first time by Boeken 1919, and have functioned as the chief arguments for every serious attempt at dating ever since. As, of course, the size of the plans to be produced was related to the format prescribed by the commissioners. Unfortunately, however, one art historian, Wouter Kuyper, has almost totally disregarded these facts.In two short articles published in 1976 and 1977 as well as in a professed handbook to seventeenth-century Dutch architecture - his widely consulted ‘Dutch Classicist Architecture’, published in 1980 - he presented his own theses for authorship and dating.As regards the former, they were very speculative and as regards the latter often very arbitrary, and moreover partially conflicting, since his interpretation is not only in conflict with the most logical order, but in each instance his next interpretation also differs from the one given before. And this without commenting on it, let alone arguing these changes.What is worse, in order to arrive at his conclusions, he not only repeatedly ignored and concealed the clearly stated sizes in the respective solutions which did not fit in with his own variable interpretations, he also more or less falsified the facts in his manual at least on one occasion, in order to arrive at this utterly unfounded 'reconstruction' of an Italianate Dam-Square project by Constantijn Huygens, to whom Kuyper attributes the so-called Monogram-style Design, but whose interference is completely hypothetical.Notably, in order to get his design integrated into a site plan made by Danckerts he tacitly increased its size. Consequently, there is every reason to examine the way in which Kuyper arrives at his conclusions, which have never before been explicitly challenged by other scholars.Hence this historiographical article which analyses all the arguments that have been put forward since the beginning of the debate for dating and attributing the projects known, in an attempt to formulate the most reasonable solution to the partly still open questions raised by this very complicated matter